Investigating the anti-hypolipidemic effects of croissants enriched with fruit byproducts in a rat model - Hanan E Mohamed; Shimaa M. Mansour; Ahmed K. Aldhalmi; Manal M. Shehata; Gehan A. El-Shourbagy; Garsa Alshehry; Eman H. Algarni; Sameh A. Abdelnour (npj Science of Food)
Abstract This study assessed the impact of partially replacing wheat flour in croissants with 10% or 15% orange peel (OP), watermelon rind (WR), or melon peel (MP) on sensory properties, in vitro antioxidant capacity (DPPH, total phenolics, flavonoids), and anti-hyperlipidemic activity in rats. Nine groups of rats: a control group (G1), a hyperlipidemic (G2), control diet + 40% croissants (G3), and hyperlipidemic diet and croissants enriched with 10% or 15% of OP (G4, G5), WR (G6, G7), and MP (G8, G9), respectively. OP exhibited the highest antioxidant activity, total phenolics, and flavonoids. Sensory evaluations indicated no significant differences among the croissant treatments. G9 and G7 significantly reduced body weight gain. All treated groups attenuated elevated blood lipid and hepatic enzyme levels compared to G2. G2 showed severe steatosis, necrosis, vacuolation, and inflammatory infiltration in the liver, while these lesions were substantially ameliorated in the treatment groups. Cardiac tissue in G2 presented with fat globules, cardiomyocyte damage, and inflammation, whereas fruit byproduct treatment effectively maintained normal cardiac tissue morphology. This study successfully demonstrated the feasibility of developing anti-hyperlipidemic functional foods by enriching croissants with fruit byproducts in a rat model.